Respuesta :
Your answer should be B if you put all the common parts together you will find you can not simplify the equation any longer.
Answer: the correct option is (B) [tex]-2x^3+6x^2+6x+9.[/tex]
Step-by-step explanation: We are given to select the correct polynomial that represents the following sum :
[tex]S=(-2x^3+4x^2+6)+(2x^2+6x+3).[/tex]
To find the above sum, we need to add the coefficients of the similar powers of x.
The summation is as follows :
[tex]S\\\\=(-2x^3+4x^2+6)+(2x^2+6x+3)\\\\=-2x^3+4x^2+6+2x^2+6x+3\\\\=-2x^3+(4+2)x^2+6x+6+3\\\\=-2x^3+6x^2+6x+9.[/tex]
Thus, the required sum is [tex]-2x^3+6x^2+6x+9.[/tex]
Option (B) is CORRECT.